Social, economic and cultural impediments to women participation in politics in Nigeria (2012)
Nigeria is blessed with human and material resources. Nigerian women constitute about half of the population of the country and are known to play vital roles as child- bearers, child-rearers, house workers and house-managers, community organizer and social and political activist among others. Despite the role of women, Nigerian women have encountered a number of problems while venturing into politics. This is due to some cultural stereotype, economic limitation, traditional practices and patriarchal societal structures. There is large scale discrimination from the menfolk, both in voting for candidates and in allocating political offices despite the roles women perform in the society. In the light of the foregoing, this article examines the current status of women in politics, identifies problems women face in their quest to participate in politics and lastly suggest possible measures for their political empowerment such as comprehensive political education on women’s political participation and their impact on democracy and good governance.